Vpliv novele ZUP-I na postopek uveljavljanja pravic iz sistema socialne varnosti - Lovšin, Špela (Delavci in delodajalci, 2026)
The article analyses the impact of the ZUP-I amendment on the procedures for asserting rights within the social security system. It examines key procedural changes (such as applications, service of documents, evidence and oral hearing, deadline for the appeal, the informative decision, decisions without a reasoning) and their effects on the position of the parties. The article derives from the thesis that the amendment contributes to the efficiency of administrative procedures, yet simultaneously raises questions regarding the effective accessibility of social rights and the protection of the weaker party.
Keywords: administrative procedure; novela ZUP-I; procedural guarantees; procesna jamstva; social administrative procedure; social security; socialna varnost; socialnoupravni postopek; upravni postopek; ZUP-I amendment